Refractory gunite and refractory concretes compacted using various methods / Kaitrai atsparus torkretbetonis ir kitais būdais sutankinti betonai - Goberis, Stasys; Antonovič, Valentinas (Journal of Civil Engineering and Management, 1996)
The aim of these investigations is to develop refractory gunite using local and waste materials available in Lithuania, to investigate its physical and mechanical properties and compare them with the same density and composition concrete compacted by vibration and ramming methods.In this work light (vermiculite, expanded fire clay, diatomite) and heavy (shamotte) aggregates with aluminium cement as binding material were used.The concrete samples (7×7×7 cm) were fired at various temperatures from 20°C to 1100°C.Five types of refractory gunites with different dry mixtures having a bulk density from 850 to 1500 kg/m3 have been developed. It was shown that concrete cold crushing strength depends on dry mixture bulk density and firing temperature: heavy concrete samples compacted by vibration and ramming methods are stronger, while light concrete samples made by gunning are better. The influence of temperature decreases the strength characteristics, which was confirmed by ultrasonic impulse velocity measurement results. An estimation of water requirements for concrete sample production various compacting methods is given. It was found that gunite water requirements are substantially lower than for rammed or vibrated concrete.Newly developed refractory gunite was used in furnaces as lining in an exhaust flue at Mažeikiai Oil Refinery.Article in Lithuanian.First Published Online: 26 Jul 2012